Participatory Budgeting in Local Governments:The case of kabale district local government, uganda - Eton, Marus; Perpetua, Arinaitwe; Fabian, Mwosi; Benard, Patrick Ogwel; Arthur, Sunday; Labson, Turyamushanga (International Journal of Emerging Technology and Innovative Engineering, 2019)
The study established the contribution of participatory budgeting in Kabale district local government. Using a cross-sectional research design, in which both quantitative and qualitative approaches were adopted, the study investigated 117 units; which were randomly and purposively selected from 174 subjects. The study adopted self-administered questionnaires and interview guides to collect data. Frequencies and percentages were used to analyze quantitative data while direct quotes from interviews supported qualitative analysis. Quantitative analysis was supported by software for document analysis (SPSS V 20.0). The study investigated the contribution of participatory budgeting from the viewpoints of information sharing, codes of conduct, facility for citizen complaints, and stakeholders’ consultation. The study found stakeholders’ consultation as the most important contribution of participatory budgeting. However, it was undermined by the absence of clear rules and procedures that govern budget consultative meetings. Since all the constructs used in measuring the contribution of participatory budgeting in Kabale were above average, it was concluded that participatory budgeting is practiced in Kabale district local government and is generally important. In recommendation, Kabale district local government should spell out the rules and procedures governing participatory budgeting in a statute or guideline. Secondly, the local government should consider holding several consultative meetings with various stakeholders to ensure the priorities of the common person are catered for in the budget estimates for any financial year. Lastly, the local government should consider allocating some funds to facilitate the operations of the office in charge of citizens’ complaints.